Hydroxyl radical scavengers inhibit human lectin-dependent cellular cytotoxicity. - Melinn, M (1986)
The role of oxygen-derived free radicals (ODFR) in lectin-dependent cellular cytotoxicity (LDCC) in humans was investigated. The hydroxyl radical traps thiourea, methanol, ethanol and phenol were effective in inhibiting LDCC, as was DABCO, a singlet oxygen quencher. The proposed pathway of hydroxyl radical production in living cells is either an iron catalysed Haber-Weiss reaction or a Fenton reaction. The effect of inhibitors of these pathways was investigated. The superoxide anion scavengers superoxide dismutase, ferricytochrome c and Tiron were without effect. It was shown that Tiron inhibits the lucigenin-amplified chemiluminescence produced by the action of xanthine oxidase, and also the lucigenin-amplified chemiluminescence produced by activated PMN, suggesting that this agent (Tiron) scavenges intracellular superoxide anion. Catalase gave slight inhibition of LDCC only. The ferric iron chelator desferrioxamine gave no protection of the target cells, while the ferrous chelator, 1,10-phenanthroline, inhibited LDCC and partially prevented the detection of hydroxyl radicals generated by the Fe2+-H2O2 system. Cibacron blue, an agent that inhibits NAD(P)H linked enzymes, also inhibited LDCC. The cyclo-oxygenase inhibitors indomethacin and salicylate were without effect, while the lipoxygenase inhibitor nordihydroguaiaretic acid (NDGA) inhibited cytolysis. None of the LDCC inhibitors was cytotoxic to the effector cells or to the target cells, neither did they inhibit lymphocyte-target binding. The findings would suggest that hydroxyl radicals have a role to play in human T-cell mediated cytolysis, either as the active lytic agent or as an epiphenomenon.